2016
DOI: 10.5815/ijwmt.2016.05.05
|View full text |Cite
|
Sign up to set email alerts
|

A Compact, Tri-Band and 9-Shape Reconfigurable Antenna for WiFi, WiMAX and WLAN Applications

Abstract: This paper introduces a novel 9-shaped multiband frequency reconfigurable monopole antenna for wireless applications, using 1.6 mm thicker FR4 substrate and a truncated metallic ground surface. The designed antenna performs in single and dual frequency modes depending on switching states. The antenna works in a single band (WiMAX at 3.5 GHz) when the switch is in the OFF state. The dual band frequency mode (Wi-Fi at 2.45 GHz and WLAN at 5.2 GHz) is obtained when the switch is turned ON. The directivities are: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…In terms of size, the proposed antenna is more compact than other antennas reported in [32][33][34][35][36][37][38]. The proposed antenna has impedance bandwidth ranges 190-1400 MHz which offers larger bandwidth than antennas designed in [32,33,[35][36][37][38][39] and has better gain than the work reported in [32][33][34]36,37,39]. The most prominent distinction, as compared to other candidate antennas, is the ability of proposed antenna to operate on nine different frequency bands, which are more than the number of bands achieved in all reported In terms of size, the proposed antenna is more compact than other antennas reported in [32][33][34][35][36][37][38].…”
Section: Surface Currentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of size, the proposed antenna is more compact than other antennas reported in [32][33][34][35][36][37][38]. The proposed antenna has impedance bandwidth ranges 190-1400 MHz which offers larger bandwidth than antennas designed in [32,33,[35][36][37][38][39] and has better gain than the work reported in [32][33][34]36,37,39]. The most prominent distinction, as compared to other candidate antennas, is the ability of proposed antenna to operate on nine different frequency bands, which are more than the number of bands achieved in all reported In terms of size, the proposed antenna is more compact than other antennas reported in [32][33][34][35][36][37][38].…”
Section: Surface Currentsmentioning
confidence: 99%
“…The proposed antenna has impedance bandwidth ranges 190-1400 MHz which offers larger bandwidth than antennas designed in [32,33,[35][36][37][38][39] and has better gain than the work reported in [32][33][34]36,37,39]. The most prominent distinction, as compared to other candidate antennas, is the ability of proposed antenna to operate on nine different frequency bands, which are more than the number of bands achieved in all reported In terms of size, the proposed antenna is more compact than other antennas reported in [32][33][34][35][36][37][38]. The proposed antenna has impedance bandwidth ranges 190-1400 MHz which offers larger bandwidth than antennas designed in [32,33,[35][36][37][38][39] and has better gain than the work reported in [32][33][34]36,37,39].…”
Section: Surface Currentsmentioning
confidence: 99%
“…With a frequency range of 0.43–5 GHz, a reconfigurable antenna with a dimension of 60 × 100 mm 2 was exhibited. In Ali Shah et al, 34 there were discussions regarding a reconfigurable antenna with proximity couple feeding for WLAN and sub‐6 GHz applications. Two substrates (separated by air) with four PIN diodes made up the antenna.…”
Section: Introductionmentioning
confidence: 99%
“…The bluetooth, WiMAX and WLAN band frequencies range from 2.36 GHz to 2.5 GHz, 3.51 GHz to 3.79 GHz and 5.47 GHz to 5.98 GHz, respectively. Another study [23], has demonstrated a reconfigurable antenna design with a triple state with dual wide operating bands supporting the WLAN applications. The switching capability was achieved by using a PIN diode with triple state functionality that enabled the antenna to provide three difference frequency responses.…”
Section: Introductionmentioning
confidence: 99%